Evaluasi Tingkat Kecukupan dan Kebutuhan Fasilitas Pelayanan Kota Baru Moncongloe - istiqamah zulkarnain; Rudi Latief; Emil Salim Rasyidi (Journal of Urban Planning Studies, 2022)
Abstract. The purpose of this study is to determine the level of adequacy of service facilities in the new city of Moncongloe at this time, as well as to project the need for service facilities and the implications of the need for space in the new city of Moncongloe. This research is quantitative research), quantitative research is a process of growing knowledge that uses data in the form of numbers as a tool to find information about what we want to know, in achieving the goal of researching the availability of service facilities in Kota Baru Moncongloe currently using a quantitative approach by looking at the existing conditions and describe the distribution and services of the facilities in Kota Baru Moncongloe in the form of service facility numbers, then use a mathematical equation in the second research objective, namely to determine the need for service facilities in Kota Baru Moncongloe, researchers use a quantitative approach related to projected needs by processing data on existing conditions, needs and development projections population dynamics in the New City of Moncongloe.